A highly stable and efficient quasi solid state dye sensitized solar cell based on Polymethyl methacrylate (PMMA)/Carbon black (CB) polymer gel electrolyte with improved open circuit voltage. (1st September 2017) - Mohan, Kiranjyoti; Dolui, Swapnil; Nath, Bikash Chandra; Bora, Anindita; Sharma, Shyamalima; Dolui, Swapan Kumar
Graphical abstract: Highlights: Highly stable polymer gel electrolyte (PGE) based on polymethyl methacrylate/carbon black is prepared to fabricate DSSC. An increase in output voltage is observed when PGE is used in the DSSC in place of liquid electrolyte. This result is explained by measuring chemical capacitance from the electrochemical impedance spectroscopic data. The DSSC fabricated with PGE with 0.57% carbon black in polymethyl methacrylate shows 5.52% photo-conversion efficiency. The DSSC also exhibits very good long term stability. Abstract: Dye sensitized solar cells (DSSCs) have received significant attention due to their low production cost and easy fabrication process. However, the leakage and volatilization of the liquid organic solvent in the liquid electrolyte affect the long term stability of DSSCs. Therefore, in this present work, to improve the durability of DSSCs, polymethyl methaacrylate (PMMA) based polymer gel electrolyte (PGE) with different weight percent of carbon black (CB) was studied to replace the conventional liquid electrolyte. CB was used to improve the ionic conductivity of the PGE. DSSCs fabricated with the prepared PGEs exhibit very good long term stability in comparison to liquid electrolyte. The optimized DSSC with 0.57 weight percentage of CB in PMMA polymer matrix exhibits the highest photo-conversion efficiency of 5.52 ± 0.03% with short circuit current density (Jsc ) value of 12.43 ± 0.04 mA cm −2, open circuit voltage (Voc ) value of 766.02 ± 0.52 mV and fill factor (FF) value of 58.01 ± 0.02%. A significant enhancement of Voc is observed with the employment of the PGE. The impact of the PGE in the enhancement of Voc was studied by analyzing the charge transfer kinetics data at the interface of the photoanode and the PGE. Furthermore, the study of long term stability shows that after 1000 h of testing the optimized DSSC (PGE(0.57)) retains the Jsc value at 83% of the initial performance exhibiting very significant long term stability in comparison to the DSSC fabricated with liquid electrolyte.